Pengaruh Asimetri Informasi dan Iklim Kerja Etis terhadap Budgetary Slack - Janet Anneta (Jurnal Bisnis dan Akuntansi, 2022)
Budgeting is one of the activities that must be carried out by the organization in order to achieve goals and performance effectiveness. The budget can act as a short-term planning and control tool for the company. However, in practice, managers can prepare a budget according to actual conditions and the best estimates that can be obtained honestly. This can happen when there is a conflict of interest and opportunistic behavior from managers in budgeting that can create budgetary slack. This research is an experimental study to examine and analyze the effect of information asymmetry and ethical work climate on the creation of budgetary slack. This study uses a 2x2 between subject research design with students of the Accounting Department at Widya Mandala Catholic University class 2017, 2018, and 2019 as research participants. The instrument given to the participants was a production task to translate letters into numbers. Testing the hypothesis in this study using the two-ways ANOVA tool. The results of this study indicate that information asymmetry has positive effect on budgetary slack, while the ethical work climate and the interaction between information asymmetry and ethical work climate do not have a significant effect on the creation of budgetary slack.